Stress fractures - Brukner, Peter, D.R.C.O.G (Blackwell Science Asia, 1999)
"Advances in nuclear isotope scans, CT scans and MRI have enabled stress fractures to be detected and identified much more easily in recent times. Written by three leading authorities in this area, Stress Fractures covers the pathophysiology, epidemiology, risk factors and treatment associated with these types of sports injury." "The book provides both theory about development of stress fractures and practical management of the various types and sites of stress fracture. It is therefore an essential reference for all clinicians who are involved in management of these injuries."--BOOK JACKET.